Whole-Body [18F]-FDG-PET/MRI for Oncology: A Consensus Recommendation - Umutlu, Lale; Beyer, Thomas; Grueneisen, Johannes Stefan; Rischpler, Christoph; Quick, Harald H.; Veit-Haibach, Patrick; Eiber, Matthias; Purz, Sandra; Antoch, Gerald; Gatidis, Sergios; Nikolaou, Konstantin; Schaefer, Jürgen F.; Rausch, Ivo; Herrmann, Ken; Vorstand der Interdisziplinären AG für Hybride Bildgebung in alphabetischer Reihenfolge; Herrmann, K.; Krause, B.J.; Schoenberg, S.O.; Umutlu, L.; Vorstand der Deutschen Röntgengesellschaft (DRG) und der Deutschen Gesellschaft für Nuklearmedizin (DGN) in alphabetischer Reihenfolge; Anton, F.; Antoch, G.; Hacker, M.; Krause, B.J.; Luster, M.; Neumann, S.; Schoenberg, S.O.; Vorwerk, D. (Nuklearmedizin - NuclearMedicine, 2019)
Combined PET/MR imaging (PET/MRI) was proposed for patient management in 2006 with first commercial versions of integrated whole-body systems becoming available as of 2010. PET/MRI followed the prior evolution of hybrid imaging as attested by the successful adoption of combined PET/CT and SPECT/CT since the early 2000 s. Today, around 150 whole-body PET/MRI systems have become operational worldwide. One of the main application fields of PET/MRI is oncologic imaging. Despite the increasing use of PET/MRI, little governance regarding standardized PET/MRI protocols has been provided to date. Standardization and harmonization of imaging protocols is, however, mandatory for efficient on-site patient management and multi-center studies. This document summarizes consensus recommendations on key aspects of patient referral and preparation, PET/MRI workflow and imaging protocols, as well as reporting strategies for whole-body [18F]-FDG-PET/MRI. These recommendations were created by early adopters and key experts in the field of PET, MRI and PET/MRI. This document is intended to provide guidance for the harmonization and standardization of PET/ MRI today and to support wider clinical adoption of this imaging modality for the benefit of patients.Citation Format:Umutlu L, Beyer T, Grueneisen JS et al. Whole-Body [18F]-FDG-PET/MRI for Oncology: A Consensus Recommendation. Nuklearmedizin 2019, 58: 1–9
Keywords: PET/MRI; oncology; consensus recommendations; whole-body imaging; hybrid imaging